In vitro and in vivo study of the antibacterial effects of Nigella sativa methanol extract in dairy cow mastitis - Hassan Rakhshandeh; Nassser Vahdati-Mashhadian; Mehrangiz khajekaramadini (Mashhad University of Medical Sciences, 2011)
Objective: Nigella Sativa (N. Sativa) seeds were used in traditional medicine for the treatment of a variety of diseases. The seed extracts and oil of this plant have shown various pharmacological properties including antimicrobial actions. In this study, the in vitro and in vivo antibacterial effects of methanol extract of the seeds against pathogenic bacteria causing mastitis in cows have been investigated. Materials and methods: in in vivo experiments, 10 cows with mastitis were treated by local injection of different concentrations of methanol extract of the seeds into the infected breasts. In in vitro experiments, the microorganisms were collected from the same infected breasts and used for the assessment of the antimicrobial effects of the extract by means of agar dilution and disk diffusion methods.  Results and conclusion: The extract showed significant in vitro and in vivo inhibitory effects on causative organisms compared to standard drugs and also induced healing of the disease. This is the first veterinary experiment, to our knowledge, that investigated the antibacterial effects of Nigella sativa.